Isolating Bacterial Strains from Diabetic Foot Patients and Testing their Antibiotic Sensitivity (Bangladesh Journal of Infectious Diseases, 2025)
Background: Diabetic foot ulcers can be contaminated with a diverse range of microorganisms, including several germs that are resistant to multiple drugs.Objective: An experiment was conducted to isolate and diagnose different types of bacteria that infect diabetic foot patients.Methodology: Samples were taken from 90 diabetic patients in four hospitals in Babil, Karbala, and Diwaniyah governorates. 125 bacterial isolates were obtained from diabetic foot patients. The number of isolates was 46 Gram-positive isolates and 79 Gram-negative isolates.Results: After screening and collecting the isolates that were similar in appearance, the examination process was carried out using the Vitec 2 device. The results indicated that the gram-positive isolate Kocuria rosea had the lowest proportion of bacterial isolates, with 6.4%, while the gram-negative strain Pseudomonas aeruginosa had the highest percentage of isolates, 26.4%.Conclusion: Gram-positive bacteria were all responsive to tetracycline and gentamycin; gram-negative bacteria were sensitive to amikacin and gentamycin.Bangladesh Journal of Infectious Diseases, December 2024;11(2):138-145